Determining the Efficacy of Screw and Washer Fixation as a Method for Securing Olecranon Osteotomies Used in the Surgical Management of Intraarticular Distal Humerus Fractures. Issue 1 (January 2015) - Woods, Barrett I.; Rosario, Bedda L.; Siska, Peter A.; Gruen, Gary S.; Tarkin, Ivan S.; Evans, Andrew R.
Abstract : Objectives: The purpose of this study was to critically evaluate the efficacy of single screw and washer fixation in comparison with other methods for securing olecranon osteotomies. The hypothesis is that screw and washer fixation is a safe and effective means of olecranon osteotomy fixation with fusion and complication rates similar to other methods of fixation. Design: Retrospective review. Setting: Two Level I Urban Trauma Centers. Patients/Participants: Patients were treated within the last 20 years and received 1 of 4 types of fixation (screw and washer alone, screw and washer augmented with tension band, tension band alone, or plate and screws) after osteotomy. Intervention: Open reduction and internal fixation of OTA/AO 13B/C distal humerus fractures with an olecranon osteotomy. Main Outcome Measurements: The primary outcome measure was the presence of osteotomy union. Secondary outcome measures were olecranon nonunion, loss of articular reduction, and removal of hardware. Logistic regression was used to determine the associations between method of osteotomy fixation and removal of hardware or nonunion rates. Comorbidities were stratified using the Charlson comorbidity index. Results: One hundred sixty patients met the inclusion criteria. Thirty-nine patients underwent screw fixation alone, 47 had tension band fixation, 16 had plate fixation, and 58 had tension band and screw fixation. Screw fixation demonstrated equal or better rates of union, maintenance of reduction, absence of infection, and implant removal compared with alternative fixation techniques. Higher Charlson scores were associated with higher rates of nonunion. Conclusions: Screw and washer fixation is a safe and effective means of securing an olecranon osteotomy. Charlson comorbidity score is one factor that may influence the development of nonunion after osteotomy. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.